Optimization of mammosphere formation assay for quantification of il6-induced stemness in differentiated breast cancer cells - K. V. Nevskaya; L. V. Efimova; P. V. Korda; D. S. Dolgasheva; M. K. Ibragimova; M. E. Menyailo; E. V. Udut; N. V. Litviakov; A. G. Pershina (Сибирский онкологический журнал, 2023)
The aim of the study was mammosphere assay optimization for quantifcation of IL6-induced stemness in differentiated (СD44– ) T47D breast cancer cells.Material and Methods. The effect of three commonly used cell-detaching methods (TrypLE, accutase, cell scrapper) at various confuence (40–50 % and 70–80 %) on cell viability, phenotypic profle and mammosphere formation was tested. The cell viability was examined using AnnexinV/propidium iodide assay. The phenotypic profle was analyzed by fow cytometry with fuorescent markers CD24 and CD44.Results. Detachment of the cells using scrapper led to substantial increase in early apoptotic and late apoptotic cells in comparison with TrypLE and accutase. Dissociation with TrypLE reduced the percentage of detected CD44+ positive cells, whereas accutase saved the surface marker. The number of mammosphere and their diameter did not differ between groups. Incubation of differentiated (CD44– CD24+) T47D cells with IL-6 for 24 hours resulted in an appearance of CD44+CD24+ and CD44+CD24–/low subpopulation. Furthermore, the differentiated cells after 24 hours of IL6 exposure formed 3 times more mammospheres compared to the control.Conclusion. Usage of cells with confuence of no more than 80 % and accutase for detachment of cells is recommended for mammosphere assay. Incubation of CD44– CD24+ T47D cells with IL6 for 24 hours is suffcient for stimulation of stemness plasticity.